ESENSI SUMPAH DALAM PERSIDANGAN PERSPEKTIF FILOSOFIS - Nazah, Farida Nurun; Astutik, Eka Ayu Astri (Lex Jurnalica, 2024)
This research probes the essence of oaths in trials from a philosophical perspective, utilizing a normative juridical approach. The Oath by the witness in process during trials is a crucial element that cannot be omitted from the Indonesian legal system. The administration of oaths, according to individuals' respective religions and beliefs, embodies moral and ethical values as articulated by Aristotle and Immanuel Kant. Aristotle emphasized the oath as the foundation of trust in law enforcement, while Kant viewed the oath as a moral act demonstrating a commitment to truth. Legally, the oath is governed by the Civil Code and the Criminal Code. Oaths in trials are categorized into oaths as evidence and oaths for giving testimony, with the testimony itself serving as evidence. In practice, oaths function to enhance the veracity of testimony and exert psychological pressure on witnesses to ensure honesty. Breaching an oath can lead to legal repercussions, including sanctions under the perjury provisions of the Criminal Code. The findings of this research indicate that oaths administered during trials in court-room, is not only as legally binding evidence but also impose a moral obligation on individuals to uphold the truth. The study concludes that ethical values are of paramount importance in the administration of justice to ensure the attainment of genuine justice; meaning that the legal process is fair (procedural justice) and the outcomes are just and equitable (substantive justice).Keywords: Oath, Trial, Philosophical